Inciting Incidents: How Can We Motivate Family Conversations about Health?. Issue 12 (20th July 2020) - Sandbulte, Jomara; Beck, Jordan; Choe, Eun Kyoung; Carroll, John M.
ABSTRACT: In many families, there are obstacles to support and collaborate with one another around positive health outcomes. One obstacle in providing support to one another occurs when family members are unaware of the need. In this study, we examine aspects of family conversations about health that affect family members' decision to share (or not to share) information within the family, specifically information about sleep behaviors and medication intake. We conducted an interview study with independent living elderly parents ( n = 11) and adult children ( n = 14). We present factors that motivate and discourage family members from talking about sleep and medication within the family. We identified that some family members shift sharing behaviors following life changes that we characterize as "inciting incidents." We elaborate the concept of inciting incidents as a resource for design ideas and contribute with a synthesis of design insights for developing family-centered health technologies.